2022
DOI: 10.31106/jema.v19i1.15036
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of SMEs performance: The role of knowledge management, market orientation, and product innovation

Abstract: The role of knowledge management (KM) in the existence of Small Medium Enterprises (SME’s) has been an important aspect of entrepreneurship. However, to perform an SME may not merely rely on its knowledge but also on other aspects such as market orientation and product innovation. This study aims to contribute to the entrepreneurship literature in the context of emerging economies. This study can be classified as quantitative research by nature as the use of a survey to gather respondent data. About 211 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…The research results confirmed hypotheses H1 and H2, reinforcing the relationship between knowledge management and innovativeness (Al-Tal & Emeagwali, 2019;Medase & Abdul-Basit, 2020;Mohamad, Ramayah & Lo, 2020;Trivedi & Srivastava, 2022) and product innovation and innovativeness (Lee et al, 2019;Setiyono, Iqbal, Alfisyahr, Pebrianggara, & Shofyan, 2022). This finding also converges with Sáenz et al (2012), who highlighted that a firm's progress in codifying, organizing, storing, and retrieving knowledge would lead to availability and easiness of access to knowledge.…”
Section: And Conclusionsupporting
confidence: 83%
See 2 more Smart Citations
“…The research results confirmed hypotheses H1 and H2, reinforcing the relationship between knowledge management and innovativeness (Al-Tal & Emeagwali, 2019;Medase & Abdul-Basit, 2020;Mohamad, Ramayah & Lo, 2020;Trivedi & Srivastava, 2022) and product innovation and innovativeness (Lee et al, 2019;Setiyono, Iqbal, Alfisyahr, Pebrianggara, & Shofyan, 2022). This finding also converges with Sáenz et al (2012), who highlighted that a firm's progress in codifying, organizing, storing, and retrieving knowledge would lead to availability and easiness of access to knowledge.…”
Section: And Conclusionsupporting
confidence: 83%
“…Therefore, innovativeness mediates the relationship between the knowledge management process and innovation performance (Yu et al, 2014). The results also contribute to the findings of Urhahn & Spieth (2014), who identified a positive relationship between innovativeness and product innovation, just as product innovation is a strategic drive to bridge the gap between knowledge management and the performance of specific companies (Setiyono, Iqbal, Alfisyahr, Pebrianggara, & Shofyan, 2022). Knowledge acquisition, application, and protection were positively and significantly related to firm innovativeness (Mohamad, Ramayah & Lo, 2020).…”
Section: And Conclusionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, additional supporting drives, such as market orientation may be appropriately viewed as an endeavor to become competitive in the marketplace and may not be the primary reason to establish the supremacy of performance. Market orientation is one of the most important prescriptions that must be established; it is a method of creating strategically oriented organizations (Setiyono et al, 2022). Therefore, market orientation could be considered a mediator between KM activities and Industry 4.0 adoption.…”
Section: The Role Of Knowledge Management In Adopting Industry 4 Tech...mentioning
confidence: 99%
“…Market Orientation is an effort to translate marketing philosophy knowledge to be implemented into marketing practice (Kesuma & Istanto, 2021). Business actors try to understand what consumers need regarding the products they will provide, such as features that consumers may need more so as to attract sales and start carrying out Product Innovation (Darma et al, 2022;Setiyono et al, 2022). It is important for companies that consumers feel satisfied with the products they buy and do not get bored.…”
Section: Introductionmentioning
confidence: 99%